Density and Climate Influence Seasonal Population Dynamics in an Arctic Ungulate. Issue 3 (1st August 2016) - Mortensen, Lars O.; Moshøj, Charlotte; Forchhammer, Mads C.
ABSTRACT: The locally migratory behavior of the high arctic muskox ( Ovibos muschatus ) is a central component of the breeding and winter survival strategies applied to cope with the highly seasonal arctic climate. However, altered climate regimes affecting plant growth are likely to affect local migration dynamics of the muskox. In this study, we apply long-term local-scale data on the seasonal distribution of muskoxen in the Zackenberg Valley, Northeast Greenland, to assess the degree of climatic influence on local seasonal muskox dynamics. Specifically, we analyze how seasonal climate (temperature, snow cover), forage availability (length of growth season), and the number of adult females available per male (operational sex ratio) influence changes in the seasonal density dependence, abundance, and immigration rate of muskoxen into the valley. The results suggested summer temperature as the major controlling factor in the seasonal, local-scale migration of muskoxen at Zackenberg. Specifically, higher summer temperatures, defined as the cumulative average daily positive degrees in June, July, and August, resulted in decreased density dependence and, consequently, increase in the seasonal abundance of muskox in the valley. Additionally, a longer growth season was found to increase the seasonal abundance of muskox in the Zackenberg Valley. In contrast, changes in spring snow cover displayed no direct relation to the seasonal immigration rate. Our study suggests that access to high-quality forage is important for the short-term, local scale population dynamics of muskoxen in Northeast Greenland.